State and Trends of the Road Goods Transportation Field Development in Ukraine - KARBOVSKA, Liubov; BRATUS, Anna; LOZHACHEVSKA, Olena; ZHELEZNIAK, Ekaterina; NAVROTSKA, Tamara (Journal of Advanced Research in Law and Economics; Vol 10 No 4 (2019): JARLE Vol X Issue 4(42) Summer 2019DO - 10.14505//jarle.v10.4(42).04, 2019)
The advantages of using motor transport for transportation of goods are substantiated. On the basis of an analysis of the indicators of the volume of transported goods and the turnover of goods of motor transport in a number of countries of Europe (Austria, Great Britain, Spain, Italy, Poland, Finland, France, the Czech Republic, Sweden), reduction of activity in the field of road transportation of goods in 2013 − 2014 and its activation in 2015-2016 are established; in addition, the influence of such negative environmental factors on the activity of road transportation of goods as reduction of the trade turnover of these countries with Russia as a result of the EU sanctions, increasing competition in the road transportation market, and the strengthening of the EU requirements for rolling stock and social guarantees for transportation workers was identified. The statistical data on the volume of transported goods and goods turnover of motor and all types of transport during 2012 − 2017 in Ukraine was explored, and a number of problems were identified that hinder the development of this sphere of activity, the main of which are: low quality of transport infrastructure and, above all, unsatisfactory conditions of road communication lines and corruption in the road construction sector, resulting from inefficient management of the field of activity; low level of safety control as far as road traffic and environmental protection are concerned; environmental pollution by road transport with emissions of harmful gases and transport noise, etc. The basic areas of the development of the sphere of road transportations of goods and of the network of highways are determined.